A Proposed Healthcare Architecture using Cloud Computing in WSN Environment with a case study - Meenakshi Thalor; Yash Gharat (MultiTech Publisher, 2024)
Internet of Things (IoT) considers a future that can connect something/someone/ any service with appropriate information communication technology that it brings innovation in the fields of home, smart home, medical system, article surveillance, and logistics. Because of this inclination, this paper develops a trailblazer: Internet of Things-aware, intelligent architecture, that can be used to monitor and track patients and other related computing devices personnel, and within hospitals premises. In line with the IoT vision, we propose IoT based healthcare architecture dependent on different but complementary technologies, especially the WSN, RFID, and smart mobile, all interacting via a Constrained Application Protocol (CoAP) over low-power wireless personal area network (6LoWPAN) framework. The framework possesses the capability to gather data instantaneously in natural status and in physical conditions of patients after which it gets processed for analysis, thereby providing services to the user. The proposed model also focuses on the security aspect in the network of the healthcare system. The security model proposes IoT based medical services which comprises three security services: protection, detection and reaction services